Application of Electrical Resistivity Tomography to the detection of the Ermakia (Northern Greece) cavity system - Vargemezis, G.; Tsourlos, P.; Papazachos, C.; Kostopoulos, D. (Bulletin of the Geological Society of Greece, 2007)
Electrical resistivity tomography has been applied for the exploration of a karstic cave system at the region of Ermakia, next to the city of Ptolemais (NWt Greece). Geological investigations indicated that the main known Ermakia cave chamber "communicates " with at least one underground karstic ovoid. This evidence lead us to prospect the surrounding area by applying 2-D Electrical tomography survey on a regular grid in both x,y directions. Survey lines crossed the known cave in order to verify k the suitability of the method at the specific area and calibrate the resistivity values. Resistivity data were inverted and results were compiled in qusi3-D resistivity images. The interpreted results indicated the existence of two more chambers next to the known one which is in agreement with in-situ observations.